Effectiveness of Human Papillomavirus Vaccination on Prevalence of Vaccine Genotypes in Young Sexually Active Women in France. (23rd December 2016) - Heard, Isabelle; Tondeur, Laura; Arowas, Laurence; Demazoin, Marie; Falguières, Michaël; Parent Du Chatelet, Isabelle; ,
Abstract: Background: Effectiveness of human papillomavirus (HPV) vaccines in the context of both guidelines, which recommend vaccination at 14 years and modest vaccine coverage, is poorly documented. Methods: Residual specimens from females aged <25 years undergoing chlamydia testing were collected, together with demographic, sexual behavior, and vaccine status data. Human pappilomavirus genotypes were determined using the PapilloCheck test system. We compared vaccine type (VT; types 6, 11, 16, 18) prevalence according to vaccination status and identified factors associated with VT prevalence. Results: Of 3736 eligible samples, 822 were from vaccinated women according to immunization record, 1021 from women self-reporting vaccination, and 1893 from unvaccinated women. Adjusted vaccine effectiveness for confirmed vaccinated compared with unvaccinated women was 95.93% (95% confidence interval [CI] = 90.22–98.32) against VT HPV and 38.37% (95% CI = 12.68–56.51) against cross-reactive genotypes (HPV 31, 33, 45), respectively. Vaccine type HPV prevalence was significantly lower (0.61%) among confirmed-vaccinated women than among those who self-reported vaccination or unvaccinated women (1.76% and 15.0%, respectively). Factors associated with prevalent VT in multivariable analysis were vaccine status, positive Chlamydia trachomatis and ≥4 partners in the preceding year. Conclusion: Our study demonstrates evidence of high effectiveness of HPV prophylactic vaccines at an individual level, supporting that wider implementation will help to reduce cervical cancer and precursors incidence.